Determining the Priority of Transport Station Construction Site Using AHP Methods - Dwi Setiyo Raharjo; Sri Hartati (JEECS (Journal of Electrical Engineering and Computer Sciences), 2016)
Construction of the transport station as a node connecting the major transport systems become an obligation of government to increase the pace of development and the achievement of the area. Build the station requires careful consideration and planning, especially with regard to the rate of population movements. The main concept in determining the priority of some transport station construction site available is the choice of location were deemed urgent to be carried out construction of the transport station. Determining the level of urgency and also refers to the criteria and factors supporting of several locations that have been provided to meet the needs of society in order to facilitate the flow of people. So it has been done by the government of Situbondo to the attainment of the index of people's satisfaction with government performance, the prioritization of transport station construction site developed using Analytical Hierarchy Process (AHP) as a decision support. With Analytical Hierarchy Process (AHP) to help facilitate Situbondo regency government in making the determination of development priorities based on problem solving into a hierarchical structure that contains of objectives, criteria, sub-criteria and alternatives.